Majelis Taklim Rumah Moderasi Beragama KUA Kecamatan Tongas sebagai Upaya Aktualisasi Moderasi Beragama - Rizkiyah, Fifin Naili (Al-Jadwa: Jurnal Studi Islam, 2023)
In the context of Negara Kesatuan Republik Indonesia (the Unitary State of the Republic of Indonesia) where the people are multicultural, religious moderacy is a strategy in maintaining the national harmony and unity. The existence of Majelis Taklim Rumah Moderasi (Da’wah Forum of Religious Moderacy House) at KUA Kecamatan Tongas is interesting for further research to find out the role of Majelis Taklim Rumah Moderasi, the programs of Majelis Taklim Rumah Moderasi as means to actualize religious Moderacy, as well as the supporting and inhibiting factors of Majelis Taklim Rumah Moderasi KUA Kecamatan Tongas in the actualizing religious Moderacy. The type of research is descriptive qualitative with data collection methods namely interviews, observation and documentation. The conclusion from the results of this study is that Majelis Taklim Rumah Moderasi KUA Kecamatan Tongas has an essential role in the actualization of religious Moderacy in society. The roles are: 1) as a medium for disseminating Islamic Moderacy and Islam Rahmatan lil Alamin, 2) as a non-formal educational institution, 3) as a unifying medium of religious believers, and 4) as a mediator for religious conflicts in society. The programs of Majelis Taklim are useful for increasing and complementing knowledge and religious insights of the community and making them understand the importance of moderacy and being moderate in religion. In short, the existence of Majelis Taklim Rumah Moderasi KUA Kecamatan Tongas is a da’wah house in the context of actualizing religious moderacy in society.